The homeopathic approach to the treatment of symptoms of oestrogen withdrawal in breast cancer patients. A prospective observational study - Thompson, E.A; Reilly, D (Homeopathy, 2003)
This paper reports on an investigation of the homeopathic approach to the management of symptoms of oestrogen withdrawal in women with breast cancer. Forty-five patients entered the study. The most common presenting symptoms were hot flushes (HF) (n = 38), mood disturbance (n = 23), joint pain (n = 12), and fatigue (n = 16). Other symptoms included sleeplessness, reduced libido, weight gain, cystitis, vaginal dryness and skin eruptions. The active intervention was an individualised homeopathic medicine. Forty women (89%) completed the study. Significant improvements in mean symptom scores were seen over the study period and for the primary end-point ‘the effect on daily living’ scores. Symptoms other than HF such as fatigue and mood disturbance appear to be helped. Significant improvements in anxiety, depression and quality of life were demonstrated over the study period. The homeopathic approach appears to be clinically useful in the management of oestrogen withdrawal symptoms in women with breast cancer whether on or off Tamoxifen and improves mood disturbance. A placebo-controlled trial would be the next stage in this line of inquiry.
Keywords: homeopathy; symptoms of oestrogen withdrawal; breast cancer